Urban Eurasia. Cities in transformation. - (:unkn) unknown (DOM Publ., 2017)
Urban Eurasia. Cities in Transformation is a journey to urban spaces, places, and people in the global and highly dynamic, but often forgotten region between Europe and Asia. Intriguing photographs and evidence-based reports give a nuanced account to experiences of urban change in cities of the post-Soviet countries. Focusing on the topics of cities and networks, urban housing, economies as well as urban diversity and conflicts, the book tracks common and differentiated patterns, processes, and effects of urban developments in space and society. The multiplicity and assemblage of Soviet, pre-revolutionary and post-Soviet legacies is carved out as a key feature of Eurasian cities.
Keywords: Stadtentwicklung; Stadt; Bebauung; Wohnungsbau; Architektur; Städtebau; Stadtgestaltung; Flächennutzung; Öffentlicher Raum; Innenstadt; Wohnen; Handel; Stadtökonomie; Stadtraum; Sozialwandel; Zielkonflikt; Beispielsammlung; Transformation; Stadtumbau; Stadtsystem; Gentrifizierung; Diversität; Verdrängung; Postsozialismus; Fotografie